Fiduciary Regulation Updates to Accommodate Legal Certainty and Notary Authority in the Removal of Fiduciary Guarantees - Multahada, Indy; Anjar Sri Ciptorukmi Nugraheni; Emmy Latifah (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
This study examines the weaknesses in the regulations governing the removal of fiduciary guarantees. Although the obligation to remove is regulated in relevant laws and regulations, practice shows that thousands of fiduciary guarantees have not been removed even after being paid off, creating legal uncertainty and hindering debtors from reusing the collateral. This study aims to analyse the urgency of updating fiduciary guarantee regulations and to formulate a regulatory framework that can strengthen legal certainty, including proposals for special markings on evidence of fiduciary guarantee objects and confirmation of the authority of the parties entitled to carry out the removal. This study uses a normative-empirical research method, employing a legislative and conceptual approach, with primary legal sources (related legislation) and secondary legal sources in the form of literature and interviews. This study found a gap between regulation and practice. The results of the study indicate the need for regulatory updates, including special markings on fiduciary collateral objects, as is the practice for encumbrances, as well as the affirmation of authority to legal subjects for the removal process. Regulatory updates are expected to create a more accountable removal mechanism and increase legal certainty for all parties.